Detection of colistin resistance via four methods in multidrug-resistant Gram-negative rods isolated from blood cultures - Alhamwi, Rama; Öksüz, Lütfiye (The Journal of Infection in Developing Countries, 2022)
Introduction: The broth microdilution (BMD) method recommended for the detection of colistin resistance is labor-intensive, time-consuming, and difficult to apply in routine laboratories. Thus, various methods, such as disk elution, commercial microdilution, and rapid polymyxin-NP tests have been developed for the detection of colistin resistance. In this study, a total of 102 multi-resistant Gram-negative bacteria isolated from blood cultures were evaluated by four different methods for the detection of colistin resistance, and compared with the reference method. Methodology: For the detection of the compatibility of these methods with the reference method, categorical and essential agreements, very major, major, and minor error rates were determined. Colistin-tigecycline and colistin-meropenem combinations were investigated in colistin-resistant isolates. Results: Of the isolates, 15 (15%) [K. pneumoniae (n = 12), A. baumannii (n = 2), E. coli (n = 1)] were resistant to colistin with reference BMD method. MIC50 and MIC90 values of all isolates were ≤ 0.25 μg/mL and 16 μg/mL, respectively. The categorical agreement rates were 100% for commercial microdilution, disk elution, and RPNP test. The essential agreement rates of commercial microdilution, disk elution, and broth macrodilution were 78.4%, 86.3%, and 100%, respectively. Although there were no major errors in these methods, the macrodilution (12%) and commercial microdilution (20.6%) methods showed the most minor errors. Colistin-meropenem combination showed a 100% synergistic effect, but the colistin-tigecycline combination showed an 80% synergistic effect and 20% indifference effect. Conclusions: Disk elution and RPNP tests are suitable for routine use because they are the most efficient, easiest, low-cost, and good performance tests in detecting colistin resistance.